Malware and their diverse characteristics related to detection and analysis: A literature survey: Muhammad Taseer Suleman - Muhammad Taseer Suleman (International Journal for Electronic Crime Investigation, 2021)
The term malware refers to a specific form of software that causes damage to the computing device through data leakage and transformation, device malfunctioning, hacking, and exploitation. Typical malware can be categorized into several categories including viruses, worms, trojans, ransomware, etc. The analysis of malware helps in the categorization and behavior judgment of malware. The deep analysis of malware helps in malware detection. The current research study covers a hierarchical representation of various malware categories, different forms of detection, computing devices for malware, and a malware analysis approach. The study describes each category in detail, which helps in forming the mapping of malware analysis in detail.